Kualitas Custumer Relationship Management terhadap Loyalitas Pelanggan pada Dealer Yamaha Bahana Pagar Bandar Lampung - Hasbullah, Hasbullah; Meidasari, Evi; Isabella, Astrid Aprica (Jurnal Enterpreneur dan Bisnis (JEBI), 2022)
Currently the focus of marketing strategies that are often used by business people is to manage individual customers carefully and in detail. marketing strategy is no longer something fancy but rather an absolute necessity for it requires an idea of marketing strategy so that one can maintain its existence by using customer relationship management practices. Information and technology is now increasingly rapidly making it easier for the strategy to establish relationships with customers, Yamaha Bahana Pagar Alam dealers provide SMS services. The population in this study was 9,903 units to determine the number of samples using the Isaac and Michael Formulas obtained a total sample of 247 respondents. The results of the regression equation then the most dominant customer relationship variable influences customer loyalty at Yamaha Banaha Pagar Alam Bandar Lampung dealers is technology, this is due to the technological variables having the greatest beta coefficient values when compared with human resources and process variables.